Gegenbauer C

The Gegenbauer polynomial of degree $n$ and order $\lambda$ are orthogonal polynomials defined to be the coefficient of $t^n$ in the expansion of $\dfrac{1}{(1-2xt+t^2)^{\lambda}}$ in the sense that $$\dfrac{1}{(1-2xt+t^2)^{\lambda}} = \sum_{k=0}^{\infty} C_k^{\lambda}(x)t^k.$$

Properties

Theorem: The Gegenbauer polynomials satisfy the differential equation $$(1-x^2)\dfrac{d^2y}{dx^2} -(2\lambda+1) x \dfrac{dy}{dx} + n(n+2\lambda)y=0.$$

Proof:

Theorem: The following formula holds: $$C_n^{\lambda}(x) = \displaystyle\sum_{k=0}^{\lfloor \frac{n}{2} \rfloor} (-1)^k \dfrac{\Gamma(n-k+\lambda)}{\Gamma(\lambda)k!(n-2k)!} (2x)^{n-2k}.$$

Proof:

Theorem (Orthogonality): The following formula holds: $$\displaystyle\int_{-1}^1 (1-x^2)^{\lambda-\frac{1}{2}} C_n^{\lambda}(x)C_m^{\lambda}(x) dx = 2^{1-2\lambda} \pi \dfrac{\Gamma(n+2\lambda)}{(n+\lambda)(\Gamma(\lambda))^2\Gamma(n+1)}\delta_{mn},$$ where $\delta_{mn}=0$ if $m\neq 0$ and $\delta_{mn}=1$ when $m=n$.

Proof:

Theorem: The following formula holds: $$(n+2)C_{n+2}^{\lambda}(x)=2(\lambda+n+1)xC_{n+1}^{\lambda}(x)-(2\lambda+n)C_n^{\lambda}(x).$$

Proof:

Theorem: The following formula holds: $$nC_n^{\lambda}(x) = 2\lambda(xC_{n-1}^{\lambda+1}(x) - C_{n-2}^{\lambda+1}(x)).$$

Proof:

Theorem: The following formula holds: $$(n+2\lambda)C_n^{\lambda}(x) = 2\lambda(C_n^{\lambda+1}(x)-xC_{n-1}^{\lambda+1}(x))$$.

Proof:

Theorem: The following formula holds: $$nC_n^{\lambda}(x) = (n-1+2\lambda)xC_{n-1}^{\lambda}(x) - 2\lambda(1-x^2)C_{n-2}^{\lambda-1}(x).$$

Proof:

Theorem: The following formula holds: $$C_n^{\lambda '}(x) = 2\lambda C_{n+1}^{\lambda+1}(x).$$

Proof:

Orthogonal polynomials